The prevalence of type 2 diabetes in South Africa: A systematic review - Pheiffer, Carmen (University of Cape Town, 2020)
The increasing prevalence of type 2 diabetes mellitus (T2DM) poses a major threat to the health and well-being of South Africans. Effective interventions to inform health planning and policy are hampered by the paucity of accurate national epidemiological data. Although several prevalence studies have been conducted, these estimates are not representative of the South African population or are sub-optimal due to the diagnostic methods employed. To address the lack of accurate and representative prevalence data, the aim of this dissertation is to use robust systematic review methods to collate, synthesise and summarise all T2DM prevalence data in South Africa. The dissertation comprises of four parts. Part A contains the study protocol that was published in BMJ Open in 2018. The protocol outlines the problem statement, motivation and rationale, aim, search strategy and robust systematic methods that were used to conduct the study. Part B provides an overview of T2DM enabling a broader understanding of the disease, with a focus on South Africa and the challenges of obtaining accurate T2DM prevalence estimates. We also describe prevention and management strategies for T2DM, and point to priority actions and approaches to achieve such prevention and management of T2DM. Part C consists of a manuscript that has been formatted for submission to BMJ Open and Part D is an Appendix with supporting information. This part addresses the aim of the dissertation and presents the systematic review "The prevalence of type 2 diabetes in South Africa: A systematic review". The manuscript outlines the rationale and methodologies, together with presenting and discussing the results of the systematic review. Our literature search, which included PubMed, Scopus, Web of Science and African Index Medicus, grey literature and references of included studies identified 1782 articles published in South Africa between January 1997 and May 2019. Of these, 15 met the inclusion criteria and were included in the systematic review. Heterogeneity across studies did not allow for a meta-analysis and a pooled estimate, thus results are described narratively. Some studies failed to report key methodological elements, which limited our ability to accurately appraise study quality. In conclusion, the systematic review highlights the high prevalence of glucose intolerance in South Africa and confirms the paucity of accurate and representative T2DM prevalence data. There is a need for well-designed epidemiological studies that use best-practice, uniform diagnostic methods to assess prevalence. Collaboration between public health scientists, diabetes specialists and policy makers is recommended to enable the collection of reliable national epidemiological data which can guide policy and planning towards effective diabetes prevention and management strategies.